Climate Vulnerability Literacy and Adaptive Capacity Through the Climatepreneurship Strategy in Bilato Village - Moch Rio Pambudi; Syahrizal Koem; Rakhmat Jaya Lahay (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The reality of climate change has an impact on people's lives. People need to pay attention to climate change that is happening. Climate change that occurs needs to be anticipated early on. With climate change, people need to increase their sensitivity to disaster threats. Bilato Village is located in a coastal area vulnerable to climate change's effects. The Bilato village community impacts the livelihood system due to climate change. The aim of holding the outreach is so that the Bilato village community adapts to climate change's impacts by utilizing existing natural resources besides fishing and salt. The subject of community service is the villagers of Bilato. The community service method is carried out in three ways: observation, interviews, and Focus Group Discussion (FGD). The three findings of community service include a) how to reduce the impact of climate change, b) the village government's efforts to deal with climate change, and c) the fate of fishermen affected by climate change. Based on the results, it can be concluded that climate vulnerability and adaptive capacity with the climatepreneurship strategy of socialization participants understand climate change.